HUMAN SPERM PROTEIN 116 KDA: A CANDIDATE ANTIGEN FOR IMMUNOCONTRACEPTION TECHNOLOGY - Umi Lestari; Aulanni’am Aulanni’am; Basuki B. Purnomo; Sutiman Bambang Sumitro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Spermatozoa membrane antigenic protein utilized as the substance candidate of immunocontraception has important criteria, that are only expressed in spermatozoa, cannot be found in the other tissue, and also should not have kinase activities. The observations done finally conclude 116kD, a sperm head’s protein is within the above criteria. It’s antigenic characters are shown with ability of it’s polyclonal antibody to bind the human spermatozoa, and interestingly this polyclonal antibody enable to block fertilization of other species in an in-vitro test experiments. This reseach also acquired that 116 kDa protein is specific and exists only in spermatozoa, and not in the other tissue such as spleen, kidney, pancreas, and epidydimic. This 116 kDa protein distribute along the whole area of the sperm, but mostly accumulated around the head up to the the neck. The imunohistological staining of the testis also indicate that this protein exists in the spermatid of the testes, but not be found in other somatic tissues, and it’s antibody is evidently was recognised by the goat and cow spermatozoa membrane protein resulted in blocking the fertilization of both species respectively. And the conclussion, 116 kD is Non-kinase protein specific only exists in the area of the head of human spermatozoa. It is therefore believed to be adequate candidate for antigen substance of immunocontraception technology.